2022
DOI: 10.1101/2022.02.10.479857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant phenotypic plasticity changes pollinator-mediated selection

Abstract: Many organisms change their phenotype in response to the environment, a phenomenon called phenotypic plasticity. Yet we hardly understand how such plasticity can affect biotic interactions and the resulting phenotypic selection. Here we use fast cycling Brassica rapa plants in a proof-of-concept experiment in the greenhouse to study the link between plasticity and selection. We detected strong plasticity in morphology, nectar, and floral scent in response to different soil types and aphid herbivory. We found p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Bumblebee first choices was taken as a measure of attractiveness of plants to these highly efficient pollinators 59 . Bumblebee visitations of generation one and two showed that the number of visits is highly correlated with seed set in this obligatorily outcrossing, animal pollinated plant (r784=0.70 p<0.001 68 ), and thus is a good fitness proxy. Because "relative seed set" had a zero-inflated distribution (ca.…”
Section: Discussionmentioning
confidence: 96%
“…Bumblebee first choices was taken as a measure of attractiveness of plants to these highly efficient pollinators 59 . Bumblebee visitations of generation one and two showed that the number of visits is highly correlated with seed set in this obligatorily outcrossing, animal pollinated plant (r784=0.70 p<0.001 68 ), and thus is a good fitness proxy. Because "relative seed set" had a zero-inflated distribution (ca.…”
Section: Discussionmentioning
confidence: 96%
“…First, low levels of nutrients in the soil can negatively affect seed production (Malhi and Gill, 2006). Under nutrient limitation, seed yield can be reduced, because not all fertilised ovules develop into seeds (Dorey and Schiestl, 2022). Second, alterations in the soil environment in-Effects of insect exuviae as soil amendment on pollinator performance and plant reproduction fluence plant traits that are used as signal by the plants to attract pollinators, thus affecting pollination success (Strauss and Whittall, 2006;Carvalheiro et al, 2021).…”
Section: Consequences Of the Use Of Soil Amendments For Plant Reprodu...mentioning
confidence: 99%